2004
DOI: 10.1136/hrt.2003.028167
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic stimulation with pyridostigmine protects against exercise induced myocardial ischaemia

Abstract: Objective: To determine the acute effects of pyridostigmine bromide, a reversible cholinesterase inhibitor, during exercise in patients with coronary artery disease. Design: Double blind, randomised, placebo controlled, crossover study. Setting: Outpatients evaluated in an exercise test laboratory. Patients: 15 patients with exercise induced myocardial ischaemia. Interventions: Maximal cardiopulmonary exercise test on a treadmill according to an individualised ramp protocol on three days. The first day was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…Decreased parasympathetic activity is also an independent risk factor after acute myocardial infarction (MI), 14,15 but few studies have investigated an alternative treatment targeting parasympathetic dysfunction. 16 We previously demonstrated that parasympathetic activation by electrical vagal nerve stimulation (VNS) markedly improved the long-term survival of CHF rats by preventing progressive pump failure and cardiac remodeling. 17 Despite potential differences of vagal nerve structure and function between animals effects in CHF, 22 and reported that donepezil increased vagal tone and preserved cardiac function in rats after MI.…”
mentioning
confidence: 99%
“…Decreased parasympathetic activity is also an independent risk factor after acute myocardial infarction (MI), 14,15 but few studies have investigated an alternative treatment targeting parasympathetic dysfunction. 16 We previously demonstrated that parasympathetic activation by electrical vagal nerve stimulation (VNS) markedly improved the long-term survival of CHF rats by preventing progressive pump failure and cardiac remodeling. 17 Despite potential differences of vagal nerve structure and function between animals effects in CHF, 22 and reported that donepezil increased vagal tone and preserved cardiac function in rats after MI.…”
mentioning
confidence: 99%
“…Therefore, pyridostigmine presents a potential anti-arrhythmic effect at higher heart rates, as occurs during physical exercise and mental stress. Accordingly, previous studies have shown a modulatory action of pyridostigmine on cardiovascular reactivity to exercise and stress, both in healthy subjects (18) and in patients with cardiovascular diseases (13,14,19). Whether adverse outcomes can be hampered by pyridostigmine or the sustained release version of the drug leads to a better effective action with lower side affects remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit exhibiting promising effects, edrophonium needs to be administered intravenously, precluding its prescription for regular use. Therefore, pyridostigmine, which can be administered orally and causes a dose-dependent vagomimetic effect with few side effects (13)(14)(15)(16)(17)(18)(19), is a preferable candidate for the treatment of impaired parasympathetic modulation in heart disease. As a drug that elicits a parasympathetic effect, pyridostigmine was expected to cause bradycardia in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations